Risk of complications rise with coronary artery disease and diabetes mellitus after endobronchial valve placement in severe heterogeneous emphysema. (2nd August 2021) - Fernandez‐Bussy, Sebastian; Kornafeld, Anna; Labarca, Gonzalo; Abia‐Trujillo, David; Patel, Neal M.; Johnson, Margaret M.; Reisenauer, Janani S.; Herth, Felix J.
Abstract: Background: Patients with chronic obstructive pulmonary disease (COPD) commonly have comorbidities which may impact both symptoms and prognosis. Endoscopic lung volume reduction (ELVR) with endobronchial valves (EBV) is an innovative, effective and safe treatment for patients with severe emphysema who remain symptomatic despite optimal medical therapy. Objectives: To evaluate medical comorbidities associated with increased risk of complications after EBV procedure. Method: This was a retrospective cohort review of patients with severe, heterogeneous emphysema who underwent Zephyr® EBV installation for ELVR. Demographics, baseline comorbidities, dyspnea scores, data regarding procedure, pulmonary function test, minimal clinically important difference and post‐EBV complications were recorded. Results: Of a total 82 participants, 24 were identified as having a post procedure complication. There was a significant difference in the incidence of type 2 diabetes mellitus (T2DM) at baseline (25%) in complication group compared with non‐complication group (5.1%) ( p value = 0.01 ). There was also a significant difference between baseline coronary artery disease (CAD) in those with (58.3%) or without (29.3%) complication ( p = 0.01 ). Multivariate analysis of other covariables, identified associations of both CAD and T2DM with a heightened risk of complication (adjusted OR 4.19 CI: 1.23–14.2, p value = 0.02 and adjusted OR of 6.1 CI: 1.3–26.1, p value = 0.02 respectively). Conclusions: Our study found that patients with severe, heterogeneous emphysema who undergo ELVR utilizing Zephyr® EBV and suffer complications during post‐procedure period are more likely to have CAD or T2DM as baseline comorbidity. These data suggest that baseline CAD and T2DM might be predictive of increased risk of complications following ELVR with EBV.